Use of murine L1210 and P388 lymphocytic leukemia cells in cytotoxic studies of flavonoids - Katrin Sak; Hele Everaus (International Journal of Phytomedicine, 2015)
In studies of antileukemic properties of flavonoids two murine cellular systems (L1210 and P388) are widely used beside the various established human leukemia lines. Differently from conventional clinically used chemotherapeutics, P388 cells reveal somewhat lower susceptibility towards plant polyphenolic agents than L1210 cells. Moreover, based on the cytotoxic analysis of different flavonoids, we provide some novel evidence of Burkitt`s lymphoma as a human equivalent of L1210 mouse model, enabling thus the use of L1210 murine model in development of novel antilymphoma drugs proceeding from natural polyphenols. At that, structurally different flavones can be considered as potential lead compounds; however, the most potent flavonoid described so far in B-cell lymphoma cells is the rotenoid deguelin, certainly requiring further in vitro and in vivo investigation.